A novel coupled musculoskeletal finite element model of the spine – Critical evaluation of trunk models in some tasks. (15th April 2021) - Rajaee, M.A.; Arjmand, N.; Shirazi-Adl, A.
Abstract: Spine musculoskeletal (MS) models make simplifying assumptions on the intervertebral joint degrees-of-freedom (rotational and/or translational), representation (spherical or beam-like joints), and properties (linear or nonlinear). They also generally neglect the realistic structure of the joints with disc nuclei/annuli, facets, and ligaments. We aim to develop a novel MS model where trunk muscles are incorporated into a detailed finite element (FE) model of the ligamentous T12-S1 spine thus constructing a gold standard coupled MS-FE model. Model predictions are compared under some tasks with those of our earlier spherical joints, beam joints, and hybrid (uncoupled) MS-FE models. The coupled model predicted L4-L5 intradiscal pressures (R 2  ≅ 0.97, RMSE ≅ 0.27 MPa) and L1-S1 centers of rotation (CoRs) in agreement to in vivo data. Differences in model predictions grew at larger trunk flexion angles; at the peak (80°) flexion the coupled model predicted, compared to the hybrid model, much smaller global/local muscle forces (~38%), segmental (~44%) and disc (~22%) compression forces but larger segmental (~9%) and disc (~17%) shear loads, ligament forces at the lower lumbar levels (by up to 57%) and facet forces at all levels. The spherical/beam joints models predicted much greater muscle forces and segmental loads under larger flexion angles. Unlike the spherical joints model with fixed CoRs, the beam joints model predicted CoRs closer (RMSE = 2.3 mm in flexion tasks) to those of the coupled model. The coupled model offers a great potential for future studies towards improvement of surgical techniques, management of musculoskeletal injuries and subject-specific simulations.